Pengaruh Media Digital Audiovisual Terhadap Pencegahan Perilaku Merokok Dan Napza - Waddah, Zora Ismuna Waddah; Dewi Sartika; Nanda Desreza (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Smoking among teenagers has become a very alarming phenomenon, judging from the increasing number of teenagers who smoke. Another negative impact of smoking addiction among teenagers is that it encourages them to try other negative things that give them pleasure, such as drugs (alcohol, narcotics, psychotropic drugs, and other addictive substances).  The purpose of this study is to determine the effect of audiovisual digital media on the prevention of smoking and drug abuse. The research design was quasi-experimental with a one-group pretest-posttest design. The population in this study consisted of all 52 seventh and eighth grade students, with total sampling used as the sampling technique. Data collection using questionnaires on smoking and drug abuse prevention. This research was conducted at SMP Negeri 2 Kuta Baro Aceh Besar on June 1-19, 2025. Data analysis was performed using the t-test. The results of the study show that digital audiovisual media has an effect on students' knowledge of smoking and drug abuse prevention (p value = 0.000), the effect of audiovisual digital media on attitudes towards smoking and drug abuse prevention among students (p value = 0.000), and the existence of an effect of audiovisual digital media on smoking and drug abuse prevention among students (p value = 0.000). The conclusion of this study is that digital audiovisual media has an effect on preventing smoking and drug abuse among students at SMP Negeri 2 Kuta Baro Aceh Besar.